PENGARUH MODAL, BIAYA, DAN VOLUME PENJUALAN TERHADAP KEUNTUNGAN PEDAGANG PAKAIAN BEKAS DI KOTA TIMIKA - Natalia Tandiallo; Ignasius Narew (JURNAL ULET (Utility, Earning and Tax), 2021)
This research was conducted to examine the effect of capital, costs, and sales volume on the profits of used clothing traders in the Central Market and Bougenvile Market in Timika City. The object of this research is the value of the effect of costs and sales volume on the profits of used clothing traders in the City of Timika. The data analysis technique used is multiple linear regression analysis. The results of this study indicate only partially the cost and sales volume have a significant effect on the profits of used clothing traders in the Central Market and Bougenvile Market in Timika City with a significance level of less than 0.05, while capital has no significant effect with a significance value greater than 0.05.